Automated detection of propagating cracks in RC beams without shear reinforcement based on DIC-controlled modeling of damage localization. (1st July 2023) - Seemab, Fahad; Schmidt, Maximilian; Baktheer, Abedulgader; Classen, Martin; Chudoba, Rostislav
Abstract: In spite of an extensive research in the past few decades, design of beams without shear reinforcement is still considered to be a challenging task. With the goal of developing realistic and simple engineering models, many researchers have contributed to the development of analytical and numerical approaches that have improved the understanding of the mechanical background of shear fracture. Still, some assumptions in these approaches, such as the rigid body kinematics which relies on the assumption of a uniquely identifiable center of rotation, have raised critical questions in the scientific community that need further consideration. In this paper, an automated crack detection scheme based on DIC-controlled modeling of damage localization is developed and presented. This scheme enables an automatic evaluation of opening and sliding profiles along the crack ligament, the center of rotation between two neighboring concrete teeth, and the moment–rotation curve directly from the DIC measurements of the surface displacement. To demonstrate the feasibility and the features of the developed scheme, verification studies are performed using tests performed on longitudinally reinforced concrete beams. The description of the mathematical concepts behind the developed crack detection scheme is accompanied with the explanation of the implementation method using modern Python packages for scientific computing, providing code snippets that show a straightforward translation of the mathematics into an executable code. Furthermore, a publicly available implementation of the developed scheme is provided in the form of an interactive Jupyter notebook. Highlights: Model and implementation concept for automated crack detection in RC shear zones. Immediate evaluation of the opening and sliding profiles along crack ligaments. Identification of the center of rotation between two neighboring concrete teeth. Evaluation of rotational kinematics assumption of analytical models for shear zones.